Synthesis and Biological Evaluation of a New Angiotensin II Receptor Antagonist - Zheng, H.-l.; Zhu, W.-b.; Wu, D.; Da, Y.-j.; Yan, Y.-J.; Bian, J.; Chen, Z.-l. (Drug Research, 2014)
The design, synthesis, in vitro and in vivo evaluation of (2 R,6 S)-4-({1-[2-(1 H-tetrazol-5-yl)phenyl]-1 H-indol-4-yl}methyl)-2,6-dimethylmorpholine, compound 1, as a novel angiotensin II receptor antagonist is outlined. Radioligand binding assays showed that 1 displayed a high affinity for the angiotensin II type 1receptor with IC50 value of 0.82 nM. It acted as a potent anti-hypertensive derivative (maximal reduction of mean arterial pressure of 47 mm Hg at 10 mg/kg po in spontaneously hypertensive rat producing a dose-dependent fall in blood pressure following oral administration lasting beyond 10 h. Acute toxicity tests measured the LD50 of 1 value as 2431.7 mg/kg, which is higher than Losartan (LD50=2248 mg/kg). In addition further testing showed that 1 also demonstrated efficient anti-proliferative activity in vitro and anti-prostate cancer activity in vivo were also found. Taken together this compound could be considered as an effective and durable anti-hypertension drug candidate with additional anti-prostate cancer activity. These encouraging results are deserved of further investigation towards its use for therapeutic benefit.
Keywords: angiotensin II receptor antagonist; hypertension; anti-hypertension drug; tumor; prostate cancer